Incidence of Common Transfusion Transmitted Diseases Among Blood Donors - Ahmed, Musleh Uddin; Begum, Hosne Ara; Hossain, Tozammel; Chakraborty, Prodipesh (Journal of Armed Forces Medical College, Bangladesh, 2009)
Transfusion transmitted diseases are one of the major health problem in Bangladesh. This study was carried out among 12,270 voluntary and directed donors in the transfusion medicine department of Khulna Medical College Hospital (KMCH), a teaching hospital of southern Bangladesh during the period from 1st July 2007 to 30th June 2008 to see the incidence of HIV, HCV, HBV, Syphilis & Malaria. All were voluntary and relative/directed donors. No professional donors had taken part in this donation system. Blood samples were collected in sterile dry plain test tube after predonation consent. Serum of each donor was collected by proper centrifugation within 6 hours of collection. Tests of all the samples were done within 24 hours of collection. The methods used were latex agglutination Immunochromatographic test (ICT) and reconfirmed by ELISA techniques. For malaria thick and thin film studies under microscope were done. On analyzing the results, 171 (1.39%) were found positive for HBsAg, 03 (0.024%) were positive for anti HCV, 01 was positive for anti HIV (0.008%). None found positive for Malarial parasite (MP) none were reactive for RPR test. Donation from professional blood donors are completely stopped in the transfusion medicine unit of KMCH. Mandatory screening of donated blood should be done for HIV, HBV, HCV, Syphilis and Malaria to reduce their transmission by transfusion. Key Words: Transfusion transmitted diseases, Blood donors. doi: 10.3329/jafmc.v5i1.2840 JAFMC Bangladesh. Vol 5, No 1 (June) 2009 pp.4-6